Kinematic analysis of the skillful Uke's movement during throwing - Hiranuma, Y.; Ito, Y.; Iteya, M. (Association for the Scientific Studies on Judo, Kodokan, 2023)
The purpose of this study was to clarify the skillfulness of the Uke motion during throwing from a biomechanical aspect. The subjects were two judo players who were skillful at Uke, two judo players who were unskillful, and two novice university students. We analyzed items according to the ground reaction force (GRF), the displacement of the center of mass, and the angles of the torso, ankle, and knee joints of Uke during Taiotoshi. In conclusion, the better Uke motions for Tori were as below; (1) Not moving the left or right leg in the Kuzushi and Tsukuri phase (2) Not leaning forward (not pulling back the hip) in the Kuzushi phase (3) Not bending the right knee in the Tsukuri phase (4) Keeping the center of mass higher in the Kake phase than in the natural stance